Techno-Economic Assessment of Solar Power Plants Development as Auxiliary System Supply at 150 kV Ciledug Substation - Priyatno, Dian; Sambegoro, Poetro Lebdo (ITB Graduate School Conference, 2025)
PT PLN as the largest electricity provider in Indonesia has an important role in accelerating the energy transition to achieve Net Zero Emission (NZE) by 2060 as Indonesia's commitment in the Paris Agreement. Substation as a link between electrical energy from generators distributed to consumers in the transmission system have not implemented the "green" concept in their operations. Ciledug 150 kV Substation in Tangerang has an empty land area of ​​1860 m² with a solar radiation intensity of 4.5 kWh/m²/day. The potential for solar energy in this location can be utilized to supply auxiliary system, thereby reducing the cost of burden and improving system reliability. To implement the planning of Solar Power Plant at GI Ciledug 150 kV, a study was conducted from the technical and economic aspects using the Pvsyst and HOMER. From the research results, the most optimal configuration for the planning of the development of GI 150 kV Ciledug Solar Power Plant development is the Grid PLN-PLTS scenario, The Grid PLN-PLTS configuration yielded positive values for IRR and Payback Period, which are 13.6% and 6.79 years. Meanwhile, the LCOE value of this configuration is the lowest at Rp 533.62 / kWh with an EBT fraction of 65%.